2020
DOI: 10.1088/1755-1315/549/1/012090
|View full text |Cite
|
Sign up to set email alerts
|

Local Communities Willingness to Pay for Conservation of Ecotourism Resources at Gelam Forest, Kelantan, Malaysia

Abstract: Gelam Forest significantly has a unique biodiversity composition that is not found in other areas. This unique biodiversity has high potential for ecotourism that has yet to be explored and promoted in Malaysia. The purpose of this study is to estimate the economic value of Gelam (Mellaleuca spp.) forest for being developed as one of the potential ecotourism attractions in Kelantan. The primary data were collected through face to face surveys with the local community in districts of Bachok. A total of 200 resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…As for visitor' WTP (general public and total respondent perspective), results show that bid price (BID1) are the only variable that significant at 5% level of significant. This result is similar with study done by (Mamat et al, 2020;Hassin et al, 2020). Furthermore, for local community perspective shows that visitor's WTP are influenced significantly at 5% by variable age and education level which these results can be supported by others study done by Kamaludin & Azlina (2020); Kamri (2013); Zaiton et al (2019) which the results shows that age and education gave impact on their studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As for visitor' WTP (general public and total respondent perspective), results show that bid price (BID1) are the only variable that significant at 5% level of significant. This result is similar with study done by (Mamat et al, 2020;Hassin et al, 2020). Furthermore, for local community perspective shows that visitor's WTP are influenced significantly at 5% by variable age and education level which these results can be supported by others study done by Kamaludin & Azlina (2020); Kamri (2013); Zaiton et al (2019) which the results shows that age and education gave impact on their studies.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, another study is conducted by Hassin et al (2020), aims to observe local communities' willingness to pay for the conservation of ecotourism resources at Gelam Forest, Kelantan, Malaysia. Variables used are bid price, education, and income.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, a method can be used to measure marketable goods and services, such as the Contingent Valuation Method (CVM). Hence, CVM is a method of estimation for non-market goods and services of environmental features or amenities, such as the value of particular places, the status of endangered species, recreational opportunities, scenic resources, and others [4], [5]. This method is closely related to the individual's behaviour in a hypothetical setting.…”
Section: 2mentioning
confidence: 99%
“…Unmanageable waste by tourists and the local community can result in pollution and harm the quality of water resources in the national park (Hassan & Azhar, 2017). Lack of understanding of what is the right way to practice conservation efforts of the natural environment among the local community is one of the factors that contributes to the negative impact of ecotourism (Hassin et al, 2020). According to Mandulangi and Towoliu (2019), the local community can be the main participants of a direct threat to this conserved area if they fail to participate in the development of ecotourism.…”
Section: Sustainable Tourismmentioning
confidence: 99%
“…Whereas there is no precise mention of the three pillars, the concept can be seen whereby sustainable development, in essence, is defined as that which ''vital elements are social and ecological factors, together with economic ones'' (Arushanyan et al, 2017). Brown et al (1987) found three ''prospects, or circumstances, where the term sustainability is used,'' born from their review of the literature (Hassin et al, 2020). The social aspect comes with the outlook of giving continued satisfaction of basic human needs of the individual, and the ecological part focuses on the continuation of the functioning ecosystem and productivity (Barbier & Burgess 2017).…”
Section: Three Pillars Of Sustainable Practicesmentioning
confidence: 99%